Adsorption of fluoride and DB-53 dye onto PLA/rGO nanoparticles: Mathematical modeling and statistical studies. (December 2021) - Manjunatha, C.R.; Nagabhushana, B.M.; Naryana, Anjana; Usha, P.; Raghu, M.S.; Adrsha, J.R.
Abstract: World Health Organization considered hazardous dye and fluoride removal to be an emergency issue in the water treatment process. In this investigation, fluoride and DB-53 dye adsorption was carried out using perovskite LaAlO3 (PLA) anchored with green synthesized rGO via the solvothermal process. BET characterization of PLA/rGO shows enhanced specific surface area (250 m 2 g −1 ) than PLA (5.91 m 2 g −1 ). PLA/rGO showed remarkable adsorption capacity of fluoride (qmax = 173.1 mgg −1 ) and DB-53 dye (qmax = 37.78 mgg −1 ) individually. The Fractal-like-pseudo-second order and Sips isotherm model well fitted with experimental statistical computation data R 2 (1.000). The field water studies of fluoride removal and competing ions effect proved the novelty of the material. The potentiality of the PLA/rGO is proved by fluoride removal upto six effective cycles. Further, PLA/rGO exhibited high antibacterial properties compared to PLA because of their opposite electric charged nature of bacterial cell walls and surface charge of the nanocomposite. Hence, the present material study is multifunctional and interesting in the adsorption of fluoride and DB-53 dye with antibacterial properties. Graphical abstract: Unlabelled Image Highlights: PLA/rGO nanocomposite shows higher adsorption efficacy for fluoride and DB-53 dye. FPSO order is the best kinetic model fitted at all adsorption concentrations of DB-53 dye and Fluoride with R 2 is 1.000 Sips isotherm is well followed for Fluoride and DB-53 dye. Adsorbent exhibited >90% regeneration efficiency and six cycles of reusability. The fluoride removal efficiency of PLA/rGO composite is much better compared to PLA.